KAJIAN KOROSI PADA MESIN PERKAKAS AKIBAT PERBANDINGAN COOLANT (PENDINGIN) YANG TIDAK SEIMBANG - Nota Effiandi; Yuli Yetri; Nofriadi Nofriadi (Jurnal Teknik Mesin, 2004)
One of the effort to lessen worn-out of tool machine is used by spraying coolant (mixture water and oil). Beside that dilution of coolant also function to slow down the rate of corrosion. But practically often arise damage ahead of schedule, so that old age to wear appliance become shorter. This research was conducted to dilution of coolant made with mixture irrigate faucet with oil and pure water mixture (aquades) with oil, were in the reality obtained that dilution of coolant aqueous of quicker faucet of its process of him from at using pure water. This matter was caused by pregnant faucet water of metal minerals able to form salt when mixed with oil, so that will quicken rustiness process. Later; Then for the variation of different composition in the reality more and more oil longer process rustiness happened. The corrosion at tool machine during the time was caused usage of faucet water to make dilution of coolant and also composition making of dilution of coolant imprecise.